Challenges and Motivation Influencing Work Engagement of High School Teachers in Zone 1, Schools Division of Zambales - Lopez, Catherine C.; Ravana, Leila L. (Future Science / FSH-PH Publications, 2025)
Teaching is one of the most stressful occupations. Investigating the challenges and motivation influencing work engagement of high school teachers, intrinsic and extrinsic motivations are pivotal for cultivating a positive and satisfying mindset. The study aims to identify the specific challenges and motivations experienced by teachers. The researcher employed a quantitative research method The findings of the study indicate that most teacher-respondents are female, early middle-aged, married, and hold the position of Teacher I, with additional academic units towards a master’s degree. Interestingly, the teacher-respondents generally disagreed on encountering significant challenges in their work engagement. However, they unanimously agreed on the crucial role played by both intrinsic and extrinsic motivations in shaping their work engagement levels. Furthermore, the study revealed that there were no significant differences in the perceived challenges affecting teacher work engagement when respondents were grouped according to sex, age, civil status, teaching position, or highest educational attainment. These findings shed light on the demographic profile of teachers in the area under study and emphasize the importance of intrinsic and extrinsic motivators in fostering their engagement in the workplace. The study identified significant differences in teacher motivation based on their attitudes towards the teaching profession and the level of autonomy support they received. In response to these findings, the proposed intervention plan aims to tackle the identified challenges in work engagement and enhance teacher motivation. By addressing these issues, the intervention plan seeks to create a more supportive and motivating environment for teachers.